Polyunsaturated fatty acids sensitize human colon adenocarcinoma HT-29 cells to death receptor-mediated apoptosis - Hofmanová, Jiøina; Vaculová, Alena; Kozubík, Alois (Cancer letters, 2005)
The proliferative and apoptotic response to TNF-alpha and anti-Fas antibody (CH-11) in human colon adenocarcinoma HT-29 cells was modulated by pretreatment with arachidonic (AA, 20:4, n-6) or docosahexaenoic (DHA, 22:6, n-3) fatty acids, which alone increased reactive oxygen species production and lipid peroxidation, and decreased the S-phase of the cell cycle. The higher amount of floating cells, subG0/G1 population and apoptotic cells detected in pre-treated cells was potentiated by cycloheximide. The effects of CH-11 were associated with activation of caspase-8, -9, and -3, cleavage of poly(ADP-ribose)polymerase-PARP, and decreased mitochondrial membrane potential (MMP), but these parameters were not significantly changed after PUFA pretreatment.
Keywords: proliferace buněk; apoptóza; Poly(ADP-ribose) Polymerases; Mitochondria; Tumor Necrosis Factor-alpha; Apoptosis; kyseliny dokosahexaenové; Collagen Type XI; nádory tračníku; poly(ADP-ribosa)polymerasa 1; lidé; kolagen typ XI; Antibodies; Reactive Oxygen Species; peroxidace lipidů; mitochondrie; Colonic Neoplasms; kyseliny arachidonové; Lipid Peroxidation; TNF-alfa; Adenocarcinoma; Poly (ADP-Ribose) Polymerase-1; adenokarcinom; Cell Proliferation; reaktivní formy kyslíku; poly(ADP-ribosa)polymerasy; Arachidonic Acids; protilátky; Docosahexaenoic Acids; Humans